Caracterização das vítimas envolvidas nos acidentes de trânsito no município de Goiânia – GO - Costa, Ludmila de Araújo (2016)
Traffic accidents are the leading cause of death and presents itself as a serious public health problem. According to data from the World Health Organization (WHO) estimates that approximately 1.2 million people die each year due to injury.In Brazil, traffic accidents are the main cause of death in the range of 1 to 19 years, the second leading cause in the range of 20 to 39 years behind the murders and Goiania is considered the third capital of the country that kills in a traffic accident in the age group 15-29 years. In this context, a survey was conducted in order to characterize the profile of the victims of traffic accidents in Goiania – GO, in the periods 2009, 2011 and 2014, notified by the VIVA Survey. The research is characterized as descriptive, cross-sectional and quantitative approach. The victims are mostly males, with percentage average of the three years studied, 70.87% compared to 29.13% for females. Most of the victims has aged 20-39 years (mean 56.64%), drivers of vehicles, mostly motorcycles, which occurred on weekends. Motorcycles were the biggest cause of accidents, both in males and in females. The head / face, the upper limbs and the lower members were parts of the body most affected victims goianienses and the head injury and fractures found in most pedestrian, cyclists and motorcyclists. This study contributes to expose the health situation related to traffic accidents, in Goiania, for researchers, managers and civil society to adopt effective measures, especially preventive.